1986
DOI: 10.1159/000156275
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Testosterone Concentrations during Postnatal Development in the Male Common Marmoset

Abstract: Repeated measurements of plasma testosterone (T) were made in 56 male marmosets from the day of birth until 300 days of age and in 44 adults (>3 years). The resulting profile of plasma T during postnatal development shows higher levels during infancy (1–90 days) followed by a nadir between 100 and 170 days and then a progressive rise in T during puberty. Although T levels of up to 21 ng/ml were measured in infant males, mean levels (±SEM) were 5.4 ± 0.6 ng/ml (days 1–10), declining gradually to 1.7 ± 0.1 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
(13 reference statements)
6
20
2
Order By: Relevance
“…The body and testicular development curves that we obtained are in accordance with the typical pattern for anthropoid primates, with rapid neonatal growth, a slow juvenile phase, and a second peak of rapid development during adolescence (Plant 1988). Body mass values in the adult subjects were similar to those previously described (captivity: Abbott and Hearn 1978;wild: Araújo et al 2000) and to those of captives observed for testicular volume (Abbott and Hearn 1978;Dixson 1986). Testicular volume in infants and juveniles is similar but a rapid increase occurred between the juvenile and subadult ages, reaching, as expected, the highest values in adulthood.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The body and testicular development curves that we obtained are in accordance with the typical pattern for anthropoid primates, with rapid neonatal growth, a slow juvenile phase, and a second peak of rapid development during adolescence (Plant 1988). Body mass values in the adult subjects were similar to those previously described (captivity: Abbott and Hearn 1978;wild: Araújo et al 2000) and to those of captives observed for testicular volume (Abbott and Hearn 1978;Dixson 1986). Testicular volume in infants and juveniles is similar but a rapid increase occurred between the juvenile and subadult ages, reaching, as expected, the highest values in adulthood.…”
Section: Discussionsupporting
confidence: 86%
“…Increased testicular volume in adults is related to increased spermatogenetic activity, testosterone production, and spermatozoid maturation (Li et al 2005). The relatively high testicular volume in the infantile stage is also coincident with the peak of testosterone production from birth until the 110th day in male common marmosets (Dixson 1986). It is important to note that we measured the testis when the individuals were 3-5 mo old because the fully descended testes in callitrichids occurs around then (Saguinus oedipus oedipus: 8 wk, Ginther et al 2002;Callithrix jacchus: 50-70 d, Abbott and Hearn 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In the single comparison of intratesticular with serum testosterone, taken just prior to the removal of organs, the moderate positive correlation at least rules out the assays themselves as a source of fluctuation. Extreme individual variations in testosterone concentrations have been reported previously (Dixson 1986, Lunn et al 1994. Marmosets have been shown to have sex hormone binding globulin.…”
Section: Discussionmentioning
confidence: 96%
“…Activity of the Leydig cells is maximum at birth and puberty. Between these two peaks there is a period of quiescence, reflected by testosterone production [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%